The COVID-19 pandemic and discouraged borrowers among Hungarian companies - Szabó, Zsolt (Public Finance Quarterly, 2023)
An increasing attention has been paid since the millennium to companies who have loan demand but are afraid of refusal. The self-rationing of loan demand is also affected by the coronavirus pandemic according to the economic literature, however, there are only a few empirical studies regarding this topic. Based on the corporate surveys of the Hungarian Development Bank (MFB-INDIKÁTOR) we analyse that to what extent and to which direction did the latent loan demand of the Hungarian companies change as a consequence of the pandemic, which corporate segments reacted more sensitively to the crisis, and whether there is a measurable effect of the negative perception towards the banks to the lending decisions of the companies. On the basis of the results of cross-tabulation analyses the pandemic moderated the fear of loan application only temporarily; the behaviour of older firms, larger companies and the agricultural sector can be considered relatively stable regarding this issue; finally the role of the experiences and in many cases the negative preconceptions about the banks having a long history together play important roles in self-restraint.